AB0139 Impact of obesity on degenerative radiographic findings. (1st June 2001) - Atalay, A; Arslan, S; Çeliker, R
Abstract : Background: Obesity is a growing problem in all countries which is considered to be one of the most important concerns for public health. For clarification of the topic, further research about morbidity of the problem should be considered. Objectives: The purpose of this study was to assess degenerative radiographic findings of the spine, pelvis and knees related with obesity. Methods: 71 female patients from our outpatient clinics were enrolled in the study. Cut-off points for obesity were determined according to guidelines of World Health Organisation (WHO). Cut-off values are as follows: 18.5–24.99: normal, 25.0–29.99 grade1 overweight, 30.0–39.99 grade 2 overweight, > = 40.0 grade 3 overweight. Beside demographic data, radiologic assessment by plain radiographs of the spine, pelvis and knees were obtained. Antropometric measurements including height, body weight, abdominal circumference, waist circumference, triceps skinfold thickness were performed by the same physician. Body mass index (BMI) was calculated as kg/m 2 . Radiographs were evaluated by a physician blind to the clinical status of that particular patient. For radiologic evaluations Kellgren-Lawrence score was utilised. p < 0.05 was considered to be statistically significant. Results: The mean age of the subjects was 52.70 ± 11.25 years (range: 25–78 years) and mean BMI was 31.17 ± 5.70 (range: 21.91–47.27). Degenerative changes in lumbar spine and knees are shown in Table 1 . BMI was positively correlated with degenerative changes in the knee even when controlled for age (p = 0.000). Radiographs of the knee was also found to be correlated with body weight abdominal circumference, waist circumference, triceps skinfold thickness. Radiologic score of the knees were found to be correlated with scores of the pelvis and lumbar spine. But radiologic scores of pelvis and lumbar spine were not correlated with antropometric measures. Conclusion: Radiographic findings in the knee was found to be correlated with BMI and other anthropometric measures when controlled for age but there was no correlation between obesity and radiographs of the pelvis and lumbar spine. References: Felson DT, Zhang Y, Anthony JM, et al . Weight loss reduces the risk for symptomatic knee osteoarthritis in women. Ann Intern Med. 1992;116:535–9 Sharma L, Lou C, Cahue S, et al . The mechanism of the effect of obesity in knee osteoarthritis. Arthritis Rheum. 2000;43:568–75 Stürmer T, Günther KP, Brenner H. Obesity, overweight and patterns of osteoarthritis: The Ulm Osteoarthritis Study. J Clin Epidemiol. 2000;53:307–13